Fluticasone propionate in chronic rhinosinusitis with nasal polyps (CRSwNP): an artificial intelligence-driven consensus - Avallone, Emilio; Iannella, Raffaella; Lullo, Antonella Di; Grasso, Michele; Musto, Salvatore; Piermichele Troncone, Enzo; Tortoriello, Giuseppe; Cassiano, Bernardino; Nappi, Simona; Bava, Gianluca; Piazzetta, Giovanna; Tomacelli, Giovanni; et al. (Frontiers in Allergy, 2025)
IntroductionFluticasone propionate (FP) is a topical corticosteroid used to treat rhinosinusitis with nasal polyposis (CRSwNP). However, the need for a consensus on its use stems from the increasing focus on optimizing topical therapies to improve clinical outcomes and minimize systemic side effects.Materials and methodsThe Butterfly Decisions AI platform facilitated the collection and integration of evaluations and feedback, facilitating an expert consensus on 13 statements.ResultsThe participants agreed highly on the different statements. The experts agreed that FP effectively reduces the need for surgery and controls the symptoms of CRSwNP. The use of advanced delivery systems significantly improved drug delivery and therapeutic outcomes. Treatment with FP was associated with a reduction in the recurrence of nasal polyps and an improvement in the patient's quality of life.ConclusionsFP, as other equal corticosteroids, represents a first-line local therapy for patients with CRSwNP without complicating comorbidities due to its high efficacy and low systemic bioavailability. The Butterfly Decisions platform has demonstrated the effectiveness of integrating AI tools into clinical decision-making, improving the transparency and objectivity of assessments.